(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
One of the common mental illnesses that affect people worldwide is depression. It can impact people from all backgrounds and age groups. Despite having medications for depression very few people respond to it in efficient manner. Currently used antidepressants show side effects like urine retention, nausea, weight gain, cardiovascular disorders, etc. To eradicate these side effects natural compounds are being evaluated for their therapeutic potentials. Metabolites obtained from marine organisms possess diverse beneficial effects. Wide variety of sponges, corals, seaweeds contains compounds with magical properties to heal mental disorders. This study demonstrates molecular docking of serotonin transporter (SERT) with some marine alkaloids. Results generated from PyRx virtual screening software shows that out of thirteen selected alkaloids only Gelliusine A have higher binding affinity than prescribed antidepressant Paroxetine. According to SwissADME, most of the selected alkaloids showed better Absorption, Distribution, Metabolism and Excretion (ADME) properties. But Gelliusine A has low gastrointestinal absorption and does not cross Blood Brain Barrier (BBB). Further optimization and experimental investigations of these compounds are needed to enhance their properties to become better antidepressants against reuptake of serotonin.